Unicentric form of Castleman´s disease, pitfalls of diagnosis and surgical treatment - Molacek, Jiri; Treska, Vladislav; Skalicky, Tomas; Vodicka, Josef; Ferda, Jiri; Ferdova, Eva; Baxa, Jan; Mach, Christiana; Jungova, Alexandra; Michal, Michael (Frontiers in Oncology, 2023)
Background: Castleman´s disease is an extremly rare heterogenous lymphoproliferative pathology with a mostly benign behaviour. It is a localized or generalized lymph node enlargement of an unknown aetiology. Unicentric form is typically a slow-growing solitary mass occurring mostly in the mediastinum, abdominal cavity, retroperitoneum, pelvis and neck. Aetiology and pathogenesis of CD is probably diverse, varying in different types of this heterogeneous disease. Materials and Methods: Authors present a review of this issue based on their extensive experience. The aim is to summarize the crucial factors in the management of diagnostics and a surgical treatment of the unicentric form of Castelman´s disease. One of the key issues in the unicentric form is precize preoperative diagnostics and thus choosing the right surgical treatment strategy. Authors highlight pitfalls of the diagnosis and surgical treatment. Results: All histological types such as a hyaline vascular type, plasmacytic type and a mixed type are presented as well as options of surgical and conservative treatment. Differential diagnosis and malignant potential is discussed. Conclusion: Patients with Castleman´s disease should be treated in the high volume centers, with a great experience in major surgical procedures as well as with preoperative imaging diagnostic techniques. Specialized pathologists and oncologists focusing on this issue are also absolutely necessary to avoid misdiagnosis. Only this complex approach can lead to excellent outcomes in patients with UCD.